Acute Compartment Syndrome Post‐Thrombolysis for Acute Pulmonary Embolism—A Case Report - Andrew Mpagwuni Ziblim; Mawunyo Ntumi; Nana Kwame Baah‐Adade; Samuel Ofosu Agamah; Dziwornu Kunutsor; Elizabeth Acheampong; Abdul‐Wakil Wunpini Salifu; Augustine Frimpong Marfoh; Nyagse Salifu; Ernest Ofosu‐Appiah (Clinical Case Reports)
ABSTRACT The use of thrombolysis for acute pulmonary embolism is well established. Thrombolysis poses the risk of mostly minor bleeding; however, intracranial bleeding is the most feared complication. Less recognized is the possibility of limb‐threatening complications, such as acute compartment syndrome, which need a high index of suspicion, prompt evaluation, and intervention.